Determinantes do spread bancário no Brasil - Lopes, Jerônimo Volmir Lopes (Universidade do Vale do Rio dos Sinos, 2014)
The spread is the difference that banks charge from borrowers and savers to pay. This topic is of paramount importance for the country's economy, as through loans made by banks are made the necessary investment to economic growth. Since 1999 the Central Bank of Brazil presents the main components of the spread, which is one of the components of the interest rate charged to borrowers, which covers the costs of financial institutions, pays savers and banks. The subject matter is presented in several studies, but without a consensus among the authors, with the interest rate of return on government bonds (Selic), along with the default rate, the major influences on the spread charged by banks Brazilians. Even with the decline in interest rates domestically and internationally in recent years after the crisis of 2008 the rates charged by financial institutions remain at a high level, but with changes in the composition of the spread.
Keywords: Taxa de juros; Spread; Rate of interest; ACCNPQ::Ciências Sociais Aplicadas::Economia